Effectiveness of the application of a digitalized repository on the quality of graduate and post-graduate education in the field of physical medicine and rehabilitation - Koleva, Ivet B.; Yoshinov, Borislav R.; Yoshinov, Radoslav R. (Frontiers in Medicine, 2025)
BackgroundDuring last ten years, we have developed a digital library with educational materials in Physical medicine and rehabilitation.ObjectivesThe objective of current article is the preparation of an electronic library with educational materials in the area of physical medicine, physical therapy and rehabilitation, and the comparative evaluation of the impact of this repository on the quality of education of students and trainees in the field.MethodologyThe electronic library includes e-books on different topics, elements of the specialty “Physical and rehabilitation medicine (PRM)” or Physiatry – with theoretical data, practical issues and case reports with videos of real patients. From the field of basic physiatry we included: books on kinesiological and pathokinesiological analysis, functional evaluation; physiotherapy (active exercises, soft-tissue techniques), ergotherapy (activities), balneotherapy (mineral baths and peloids, underwater gymnastics), manual therapy (tractions, mobilizations, manipulations), preformed physical factors (electric currents, magnetic field, ultrasound, light, laser, etc). In special physiatry we prepared manuals on: neurological and neurosurgical rehabilitation, orthopedic and traumatologic rehabilitation, rheumatologic rehabilitation, cardiac and cardiosurgical rehabilitation, etc. The digital library has been applied to educate 1,186 learners (graduate and post-graduate studies): students in Bachelor’s degree (Physiotherapy, Nursing, Midwifery, Medical assistants) and in Master’s degree (Physiotherapy, Medical rehabilitation and balneology), medical doctors—residents in Physical and Rehabilitation medicine (PRM), participants in long-life learning courses (physiatrists, physiotherapists and nurses). At the end of every educational course, we collected data from the practical and theoretical exams (investigation period—from April 2020 to October 2024). Additionally, we evaluated learners’ opinion using anonymous questionnaires on the usefulness of the electronic library.ResultsComparative analysis of the results revealed significant improvement in theoretical knowledge and practical skills of students and trainees, as evidenced by online assessments, and face-to-face theoretical and practical exams. The majority of learners consider the electronic repository useful.Conclusion and recommendationsThe authors consider this electronic library (with books, manuals, video-presentations and case studies) a valuable resource in both graduate and post-graduate education within the rehabilitation field. We recommend the application of electronic repositories in the process of education of the students and trainees.